Pemanfaatan Batok Kelapa Untuk Meningkatkan Kreativitas dan Motorik Kasar Anak Usia Dini - Fadilla, Rohayu; Margaretha, Lydia; Jusmadi, Evryeni; Mayasari, Henni; Auliya, Sentiya; Putri, Meyzi Yolanda (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
Not all Early Childhood Education schools utilise coconut shells as a learning medium, especially in increasing creativity and gross motoric early childhood, especially in Seluma Regency Institutions, this is one of the reasons for Dehasen University Bengkulu lecturers and students to carry out community service activities (PKM). Aiming to analyse how the use of coconut shells to improve creativity and gross motoric of early childhood in Seluma district. From the results obtained in this PKM activity, kindergarten teachers gain knowledge about the use of coconut shells to increase creativity and gross motoric of early childhood and kindergarten teachers become more creative in utilising teaching media so that children are not bored in the teaching and learning process.